Blockchain in supply chain management: Characteristics and benefits - Eladian Rodrigues (Associação Nacional de Pós-Graduação e Pesquisa em Administração (ANPAD), 2021)
The basis for application of new technologies in organizations is supported by the continuous analysis of data and information from multiple sources. Blockchain is one of the new technologies that, in association with the concepts and principles of Industry 4.0, could generate gains and improvements. Much has been said about the potential of blockchain technology, its benefits, and its disruptive impact in various areas, including supply chain management. In the academic field, however, the development of this topic is in full swing, as a growing number of scientific studies have been published without a theoretical convergence of their foundations, concepts, and authors being noted. Thus, considering the initial stage of the scientific debate of this object of analysis, this research aimed to understand the scenario of the adoption of blockchain in supply chain management based on academic publications evidencing its characteristics and benefits, through a systematic literature review. Due to profound analysis, characteristics and benefits of its application on supply chain management as transparency, confidence, information decentralization, and information security are disclosed in this study.